One-year outcome of robotical vs. manual percutaneous coronary intervention - Zur Mühlen, Constantin von; Jeuck, Marvin; Heidt, Timo; Maulhardt, Thomas; Hartikainen, Tau; Supady, Alexander; Hilgendorf, Ingo; Wolf, Dennis; Kaier, Klaus; Westermann, Dirk; Rilinger, Jonathan (Clinical research in cardiology, 2025)
Background: Robotic-assisted percutaneous coronary intervention (R-PCI) is a promising technology for optimizing the treatment of patients with coronary heart disease. For a better understanding of the potential of R-PCI in clinical routine compared to conventional manual PCI (M-PCI) both initial treatment success of the index procedure and long-term outcome have to be analysed. Methods: Prospective evaluation from the FRiK (DRKS00023868) registry of all R-PCI cases with the CorPath GRX Cardiology by Siemens Healthineers and Corindus in the Freiburg University Heart Center between 04/2022 and 03/2023. Index procedure success and safety, radiation dose of patients and personnel, and 1-year outcome will be reported. Findings will be compared to a prospective control group of M-PCI patients treated by the same team of interventionalists during the same observation period. Results: Seventy patients received R-PCI and were included in the registry. PCI success rate was 100%, with 19% requiring manual assistance. No complications (MACE—major adverse cardiovascular events) occurred. Compared with 70 matched-pair M-PCI patients, there was a higher median procedural time (103 min vs. 67 min, p < 0.001) and fluoroscopy time (18 min vs. 15 min, p = 0.002), and more contrast volume was used (180 ml vs. 160 ml, p = 0.041) in R-PCI vs. M-PCI patients. However, there was no significant difference of the dose-area product (4062 vs. 3242 cGycm2, p = 0.361). One year after the intervention, there was no difference in mortality, rehospitalisation, unscheduled PCI or target vessel failure. Health-related quality of life evaluation 6 and 12 months after the index procedure (NYHA, CCS, SAQ7 and EQ-5D-5L) was similar in both groups. Conclusion: R-PCI is feasible and safe. Compared to M-PCI, index procedure success rate is high, safety profile is favourable, and manual assistance was required in only few cases. At 1-year follow-up results for R-PCI vs. M-PCI considering mortality, rehospitalisation, morbidity and target vessel failure were equal.